Halal Certification Challenges in Pekalongan City's MSMEs: Tantangan Sertifikasi Halal di UMKM Kota Pekalongan - Wibowo, Dwi Edi; Prematura, Aditya Migi; Aditya, Agung; Maulana, Jaya (Indonesian Journal of Innovation Studies, 2023)
This study investigates the implementation and impact of halal certification within Micro, Small, and Medium Enterprises (MSMEs) in Pekalongan City, primarily focusing on the role of the Majelis Ulama Indonesia (MUI) in facilitating and ensuring compliance with halal certification. Utilizing a mixed-method approach, encompassing juridical-normative and juridical-empirical research techniques, we scrutinized both the legislative framework and its real-world application within Pekalongan's food and beverage MSME sector. The data revealed that the halal certification process is hindered by several factors, including insufficient human resources and a pervasive lack of understanding and awareness regarding the necessity and implications of halal certification among MSME actors. Notably, the current level of law awareness pertaining to halal certification in Pekalongan City remains suboptimal. This shortfall suggests an urgent need for enhanced educational and socialization efforts to bolster legal consciousness and promote compliance. Additionally, the research underscores a pivotal role for the MUI, not just in terms of routine inspection and conflict resolution but also as a collaborative agent working with various institutions like BPOM, the Ministry of Religion, and law enforcement agencies to safeguard consumer rights and uphold religious and legal standards. These findings stress the need for concerted multi-agency efforts to foster a more inclusive and knowledgeable halal-certified product ecosystem in Pekalongan City.Highlights: Awareness Gap: Significant lack of understanding about halal certification necessities and procedures among MSMEs in Pekalongan City. Resource Shortfall: Insufficient human resources hinder the optimal implementation of the halal certification process. MUI's Central Role: MUI's pivotal role in enhancing the halal certification process, fostering compliance, and protecting consumer rights. Keywords: Halal Certification, Pekalongan City, MSMEs, Consumer Protection, Majelis Ulama Indonesia (MUI).